SOSIALISASI TENTANG HARMONI DALAM KERAGAMAN MENUJU INDONESIA MAJU PADA MAHASISWA IIM SURAKARTA - Nissa, Izzun Khoirun; Sulistyowati, S; Safitri, Yuni (AL HAZIQ: Journal of Community Service, 2024)
This community service aims to provide socialization to internalize the value of religious moderation so that it can later be implemented during KKN in Andong District, Boyolali Regency. In addition, students also gain knowledge related to Religious moderation is actually the key to creating tolerance and harmony, both at the local, national, and global levels. The choice of moderation by rejecting extremism and liberalism in religion is the key to balance, for the sake of maintaining civilization and creating peace. In this way, each religious community can treat others with respect, accept differences, and live together in peace and harmony. In a multicultural society like Indonesia, religious moderation may not be an option, but a necessity.